HLA-B27 Status and its Association with Clinical Manifestations of Ankylosing Spondylitis in Bangladesh (East West Medical College Journal, 2026)
Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease strongly associated with HLA-B27. Data from Bangladesh on its clinical relevance are limited. This study evaluated the association between HLA-B27 and ankylosing spondylitis (AS) among axSpA patients. Methods: This cross-sectional study was conducted at the National Institute of Laboratory Medicine and Referral Centre (NILMRC), Dhaka, from March to December 2023. A total of 300 patients with suspected axSpA were included based on ASAS criteria. Demographic, clinical, and laboratory data were collected. HLA-B27 was detected using real-time PCR. ESR and CRP were measured using the Westergren method and nephelometry, respectively. Data were analyzed using SPSS version 27. Results: Among the participants, 23.7% were HLA-B27 positive and 19.7% were clinically diagnosed with AS. HLA-B27 showed a strong association with AS (OR=20.08; 95% CI: 11.56–34.86). Male gender, positive family history, and shorter disease duration were significantly associated with both AS and HLA-B27 positivity (p